The impact of the pandemic generated by coronavirus on employees in social services for seniors from Romania - Chirugu, Gianina; Tasenţe, Tănase; Rus, Ciprian-Vasile (Technium Social Sciences Journal, 2022)
Since 2020, senior social services staff have been working under new circumstances resulting from the global spread of COVID-19. The pandemic and the restrictions put in place to control it have affected every area of our lives. Thus, this paper aims to analyze the perception of employees on social services for the elderly in Romania and is based on the indicators: the degree of involvement of employees in social services for seniors, the resilience capacity of employees in social services for seniors and the impact of the pandemic on employees in social services for seniors. In order to assess the impact of the Coronavirus pandemic on social services for seniors, the employees of the service providers were invited to participate in a quantitative research based on the sociological survey based on the questionnaire with the most honest answers to each question. The design of the questionnaire was based on previous research, and adaptations were made where necessary. According to the centralization of the data obtained, the personnel employed in social assistance institutions providing social services to elderly people in our country confirm that access to protective equipment and risk management recommendations have been improved. .